2020
DOI: 10.1038/s41443-020-0322-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic evaluation of youtube as an information source for male infertility

Abstract: This study evaluates YouTube videos (YTVs) focused on male infertility to assess information quality and identify highquality content that can reliably facilitate care. Top 50 YTVs based on relevance were identified using the keyword "male infertility." A checklist, adapted from American Urological Association guidelines addressing male infertility, was developed to assess YTV content. Two investigators extracted YTV features (including duration, likes, views, upload date), classified creators and ranked YTVs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 13 publications
(14 reference statements)
2
17
0
2
Order By: Relevance
“…There are several studies in the literature evaluating the reliability of YTVs related to men's health conditions such as male infertility, premature ejaculation, erectile dysfunction, benign prostatic hyperplasia treatment, and prostate cancer that also found that most YTVs related to the evaluated subject are unacceptable as a patient education resource. 12 , 14 , 15 , 16 For example, Loeb et al found that there is widespread dissemination of misinformation about prostate cancer on YouTube and that less reliable videos had increased user engagement. 12 However, the present study is one of the only studies to show that there is reliable information on YouTube and that it could be acceptable to use as a patient education resource if patients are directed to videos featuring board-certified physicians.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies in the literature evaluating the reliability of YTVs related to men's health conditions such as male infertility, premature ejaculation, erectile dysfunction, benign prostatic hyperplasia treatment, and prostate cancer that also found that most YTVs related to the evaluated subject are unacceptable as a patient education resource. 12 , 14 , 15 , 16 For example, Loeb et al found that there is widespread dissemination of misinformation about prostate cancer on YouTube and that less reliable videos had increased user engagement. 12 However, the present study is one of the only studies to show that there is reliable information on YouTube and that it could be acceptable to use as a patient education resource if patients are directed to videos featuring board-certified physicians.…”
Section: Discussionmentioning
confidence: 99%
“…(2017; [ 70 ]) Facebook Quantitativ manuell + Profis Sonstige + 6 Gering 44 Ku et al. (2020; [ 71 ]) YouTube Quantitativ manuell + Profis Laien + 2 Gering 45 LeBeau et al. (2020; [ 72 ]) Snapchat Qualitativ Sonstige + 5 46 Levinson et al.…”
Section: Methodeunclassified
“…500 Follower/Likes Ku et al. (2020; [ 71 ]) N = 42 reichweitenstärkste, englischsprachige YouTube-Videos zu männlicher Unfruchtbarkeit 10 % der Videos (4) mit guter oder sehr guter Schulnote laut Expertenurteil 90 % der Videos (38) mit mittlerer oder schlechter Schulnote laut Expertenurteil Paul et al. (2017; [ 88 ]) N = 50 meistgesehene englischsprachige YouTube-Videos zum Hormonimplantat als Verhütungsmethode 24 % der Videos (12) von Gesundheitsprofis mit höherem DISCERN-Index (Md = 3) 76 % der Videos (38) von Patient:innen mit geringerem DISCERN-Index (Md = 2) Warren et al.…”
Section: Ergebnisseunclassified
“…This was deemed as a good and reliable source of patient information, that an ideal video should also contain. The criteria had a total score of 20 and a qualitative rating was awarded based on the reviewer's score: "Very poor" (0-5), "Poor" (6-10), "Acceptable" (11-15), and "Good" (16)(17)(18)(19)(20). The reviewer's ratings were then compared.…”
Section: On 21stmentioning
confidence: 99%